Development Studies: E-Module Based on Ethnomathematics to Improve Problem-Solving Ability at Junior High School10 Metro - Lita, Rahma Nur; Mustika, Juitaning (Universitas Sarjanawiyata Tamansiswa, 2024)
There are still many students who need help solving mathematical- problems. The need for attractive, easy-to-understand, and culture-based learning is essential for students. The objectives of this research are as follows: 1) to determine the stages of development of ethnomathematics-based e-modules, and 2) to find out whether ethnomathematics-based e-modules can improve problem-solving abilities at state junior high school 10 Metro. The research method uses a design research and development study type, including preliminary and prototyping stages (formative evaluation). According to the subject matter, media, and cultural experts, it is